Engineering a live-attenuated porcine reproductive and respiratory syndrome virus vaccine to prevent RNA recombination by rewiring transcriptional regulatory sequences - Liwei Li; Jinxia Chen; Zhengda Cao; Ziqiang Guo; Jiachen Liu; Yanjun Zhou; Guangzhi Tong; Fei Gao (mBio)
ABSTRACT Recombination is a significant factor driving the evolution of RNA viruses. The prevalence and variation of porcine reproductive and respiratory syndrome virus (PRRSV) in China have been increasing in complexity due to extensive interlineage recombination. When this recombination phenomenon occurs in live vaccine strains, it becomes increasingly difficult to prevent and control PRRSV. Reverse genetic manipulation to engineer a different transcriptional regulatory sequence (TRS) circuit introduces genetic traps into the viral genome that are lethal to recombinant RNA progeny viruses. In this study, major interlineage recombination patterns were identified between lineage 1 (L1) PRRSVs and lineage 8 (L8) PRRSVs in China, from 2019 to 2023. The recombinant mutant virus, vA-TRSall, was constructed and successfully rescued by rewiring the entire TRS circuit without changing the amino acid-coding sequence in the genome of the PRRSV live vaccine strain vHuN4-F112. The vA-TRSall, with a brand new TRS circuit, provided effective immune protection against the highly pathogenic L8 PRRSV (vHuN4) and epidemic NADC30-like L1 PRRSV (vZJqz21). Recombination analysis in vitro and in vivo showed that, compared with the vHuN4-F112 and vZJqz21 co-infection groups, the incidence rates of mutation breakpoints and template-switching recombination in the vA-TRSall and vZJqz21 co-infected groups were effectively reduced. The results have enriched our understanding of the critical role of TRS circuits in PRRSV recombination mechanisms and indicate a successful redesign that can endow PRRSV live vaccines with recombination-resistant capabilities.IMPORTANCEPorcine reproductive and respiratory syndrome viruses (PRRSVs) are genetically diverse, and this is due in part to their extensive recombination. Live vaccines are widely used to prevent and control PRRS in China. However, owing to the wide variety of live vaccines, non-standard use, and the wild viruses prevalent on pig farms, new strains, generated via RNA recombination, are continuously emerging. Vaccine strains are also involved in PRRSV recombination, which leads to the emergence of new variants and alterations in virulence and pathogenesis. A recombination-resistant genome was engineered by rewiring the entire transcriptional regulatory sequence (TRS) circuit of the live PRRSV vaccine strain. Theoretically, after clinical application, once the virus recombines with the genome of the epidemic strain, the base pairing between the two sets of TRS circuits should be disrupted, resulting in a fatal genetic trap for the generation of an RNA recombinant progeny virus. Therefore, the remodeled PRRSV TRS mutant generated in this study can serve as a recombination-resistant platform for the rational design of safe PRRS vaccines in the future.